PENGARUH PENAMBAHAN TOP SOIL INCEPTISOL DAN KOMPOS PADA TAILING AMALGAMASI TERHADAP PANJANG SULUR, DIAMETER SULUR DAN JUMLAH CABANG TANAMAN UBI JALAR (Ipomoea batatas L.) - Indra Herliana; Pujawati Suryatmana; Reginawanti Hindersah; Rhazista Noviardi (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Tailings are waste generated from the processing of gold ore. The tailings in Kertajaya Village, Sukabumi are generally dumped into a pond or garden which is then used by the community to grow crops. The characteristics of the tailings, which contain low organic matter, microorganism activity, CEC and essential nutrients, make it necessary to improve their condition. This study aimed to determine the effect of adding top soil and compost to the tailings on the growth of sweet potatoes in the vegetative phase. This experiment used a factorial randomized block design with two factors, namely a top soil-tailing ratio of 3 levels (70: 30% w/w; 50: 50% w/w; and 30: 70% w/w) and a compost dose of 4. level (without compost (control); 10 t ha-1; 20 t ha-1; and 30 t ha-1) with 3 replications. The results showed that the combination of the addition of top soil ratios and the dose of compost to the tailings had no effect on the addition of tendrils length, tendril diameter and number of sweet potato branches during the vegetative phase. The addition of 70% top soil independently on the tailings had an effect on the highest increase in tendril length, tendril diameter and number of branches of sweet potato. Meanwhile, the application of compost dosage of 30 t ha-1 had the highest effect on the number of branches Â Â of sweet potato.